Diagnostic Model Incorporating Clinicopathological Characteristics of Delphian Lymph Node Metastasis Risk Profiles in Papillary Thyroid Cancer - Li, Xingchen; Duan, Yuansheng; Liu, Dandan; Liu, Hongwei; Zhou, Mengqian; Yue, Kai; Shuai, Yanjie; Wang, Yu; Ji, Chenyan; Jing, Chao; Wu, Yansheng; Wang, Xudong (Frontiers in Endocrinology, 2021)
The Delphian lymph node (DLN), also known as the prelaryngeal node, is one component of the central lymph node. The DLN has been well studied in laryngeal cancer, although its significance in papillary thyroid cancer (PTC) remains unclear. We retrospectively analyzed 936 patients with PTC who underwent thyroidectomy by a single surgeon in Tianjin Cancer Hospital from 2017 to 2019. Moreover, 250 PTC patients who underwent thyroidectomy by another surgeon in Tianjin Cancer Hospital from January 2019 to April 2019 were used as a validation cohort. Among the 936 patients with PTC, 581 patients (62.1%) had DLNs, of which 177 samples with metastasis (177/581, 30.5%) were verified. DLN metastasis was significantly correlated with sex, age, tumor size, bilateral cancer, multifocality, extrathyroidal extension, lymphovascular invasion and central and lateral neck lymph node metastasis. Multivariate analysis revealed that independent risk factors for DLN metastasis included age, gender, tumor size, extrathyroid extension, lymphovascular invasion and central lymph node metastasis, which determined the nomogram. In particular, tumor size was proven to be one of the most predominant single predictors. The diagnostic model had an area under the curve (AUC) of 0.829 (95% confidence interval, 0.804-0.854). The internal and external validations of the nomogram were 0.819 and 0.745, respectively. Our results demonstrate that DLN metastasis appears to be a critical parameter for predicting metastatic disease of the central compartments. Furthermore, this study provides a precise criterion for assessing DLN metastasis and has great clinical significance for treating PTC.